Expression and prognosis of ADAMTS18 in different tumors - Guo, Wenfei; Zhang, Yuying (Frontiers in Oncology, 2024)
ADAMTS18 has been identified as an orphan member of the ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family of Zndependent secreted metalloproteinases since 2002. Despite the recent breakthroughs in tumor biology of ADAMTS18, there is no literature systematically discussing the relationship between ADAMTS18 and cancer. In this review, we will summarize the expression pattern and prognostic value of ADAMTS18 in various cancers. In addition, we will highlight the biological functions of ADAMTS18 in the tumor microenvironment, including the regulation of cell proliferation signals, death patterns, invasion, and migration, which influence cancer progression.